Perceptions of Ectogenesis among Prominent African and Western Feminists. Issue 2 (3rd July 2022) - Dasaolu, Babajide Olugbenga; Ofuasia, Emmanuel; Olasunkanmi, Ibiyemi Sheriff
Abstract: Medical and technological breakthroughs opened the way for ectogenesis as a way of carrying to full term foetuses that would otherwise have been lost to death. Subsequently, most Western feminists have found in ectogenesis a plausible tool for combating patriarchy. Hence, some Western feminist scholars have recently started questioning the essence of natural birth and whether it is even necessary at all, considering the bodily and psychological discomforts it entails for women. Using comparative analysis, this article engages prominent Western feminists' arguments on ectogenesis in the light of what some African feminists maintain. This article concludes that the position of most Western feminists—that ectogenesis is potentially a tool for liberation from patriarchy— is not a position held among African feminists. This article explores the positions of some prominent African feminists on ectogenesis and its implications for motherhood. The article concludes that the scholars in these two orientations have divergent views on ectogenesis because of the ideologies underlying their strands of feminism.